Self-Expression Through Art and Drumming : a Facilitator's Guide to Using Art Therapy to Enhance Drum Circles - Mank, Jen (Jessica Kingsley Publishers, 2021)
This concise book explains the theory behind drumming for therapy and gives practical guidance on facilitating drum circles. With a particular emphasis on incorporating art therapy, it provides step-by-step directions for making and painting drums from scratch with detailed photographs for clarity.